Placebo-controlled evaluation of a bioengineered, cocaine-metabolizing fusion protein, TV-1380 (AlbuBChE), in the treatment of cocaine dependence. (1st September 2016) - Gilgun-Sherki, Yossi; Eliaz, Rom E.; McCann, David J.; Loupe, Pippa S.; Eyal, Eli; Blatt, Kathleen; Cohen-Barak, Orit; Hallak, Hussein; Chiang, Nora; Gyaw, Shwe
Highlights: A placebo-controlled phase 2 study of TV-1380 in cocaine dependence is described. TV-1380 is a recombinant protein that metabolizes and inactivates cocaine. A significant increase in abstinence was not observed at the end of 12-wk treatment. A dose-dependent increase in the percentage of cocaine-free urines was observed. Abstract: Background: TV‐1380 (AlbuChE) is a novel recombinant fusion protein of mutated butyrylcholinesterase (BChE) that has increased catalytic efficiency for cocaine metabolism compared to wild-type BChE. Methods: Intra-muscular injections of TV-1380 (150 mg or 300 mg) or placebo were administered once weekly to participants (n = 66–69 per group) in a randomized, double-blind study to evaluate the ability of TV-1380 to facilitate abstinence in treatment-seeking, cocaine-dependent individuals. The primary endpoint was the proportion of participants achieving abstinence from cocaine during the last three weeks of the 12 week treatment phase, based on daily self-report of "no use" confirmed by urine testing. Results: Although there were no significant differences between the TV-1380 treatment groups and placebo for the primary endpoint, 6% of participants in the 150 mg and 300 mg TV-1380 groups and no participants in the placebo group achieved abstinence. For the only declared secondary endpoint, there was a dose-dependent increase in the group mean percentage of urine samples testing negative for cocaine metabolites during weeks 5–12 (8.1% and 14.6% for the 150 mg and 300 mg TV-1380 groups, respectively, compared to 4.7% for the placebo group; p = 0.0056 for 300 mg vs. placebo). No meaningful differences in adverse events were seen between treatment groups. Conclusions: While the apparent reduction in cocaine use may be of insufficient magnitude to justify further trials of TV-1380 in cocaine dependence, the results argue for development of improved enzymes with greater catalytic activity.